Assessment of Microbial Quality, Physiochemical Properties and Adulteration of Raw Milk in Pokhara - Gurung, Krishna; Poudel, Anupa (Tribhuvan University Journal of Microbiology, 2025)
Objectives: This study was conducted to assess the microbial quality, physiochemical properties and adulteration status of raw milk collected from different farms of Lekhanath, Pokhara, Nepal. Methods: Total of 30 milk samples (15 Cow and 15 Buffalo) were collected from five different farms of Lekhanath, Pokhara. Total coliform count, isolation and identification of Escherichia coli and Staphylococcus aureus were determined by pour plated and spread plate technique and different biochemical and enzymatic tests, respectively. Additionally, physiochemical properties and adulteration parameters were also tested. Result: The laboratory analysis revealed that, the total coliform count of raw cow and buffalo milk samples were found as 0.55´104 to 2.13´106 CFU/ml and 0.34´104 to 1.76´106 CFU/ml respectively which is higher than the DFTQC and BIS guidelines. E. coli and S. aureus were found as 40%, 13.33% and 46.67%, 33.33% for cow and buffalo milk respectively. 20% of the raw buffalo milk sample were adulterated with Neutralizer. However, no adulteration was detected for table sugar, formalin, and starch. The average fat content of cow and buffalo milk were found to be 4.13% and 5.47% respectively meeting the minimum requirement set by guidelines. The solid-not-fat and Total solid of the samples were within the acceptable limit and acidity level were within the expected range indicating proper handling and storage of the milk sample. Conclusion: Thus, the findings suggest that the raw milk samples analysed in this study may not meet the microbiological safety standards for consumption. Proper hygiene practice and quality control measures should be implemented to ensure the safety and quality of milk.